Surgical challenges of down syndrome with developmental dislocation or dysplasia of the hip undergo operative treatment under anaesthesia in teaching hospital - Prasetyo, Mika K.; Bayusentono, Sulis (International Journal of Research in Orthopaedics, 2020)
Developmental/dislocation of the hip is one of the orthopaedic issues and the most common problem of the hip in down syndrome (DS). Down syndrome often arises with its general laxity problematics, one of the things is developmental dislocation/dysplasia of the hip (DDH). In chronic cases, surgery is a must, and this is mentions in several journals. Some complications can occur in the process of anaesthesia with intubation. We report two cases, both of which are seven years old with patients in the first case experiencing DDH and patients in the second case experiencing dislocation. The first patient had open reduction surgery with capsulotomy and internal fixation. The second patient, close reduction, and hemi spica installation. The first patient has trouble breathing one week after surgery, and then the tracheotomy is performed. A tracheotomy performed for almost two months and hemi spica removed in September 2019. After hemi spica removal, the patients were then routinely controlled for rehabilitation polyclinics, and the results improved.